Konstruksi Beragama Padatarekat Syadziliyah Pondok PETA Tulungagung - Dita Hendriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Islam has recently received a negative label as a religion of violence, anarchy, terror, deviating from peace and safety, and its teachings are considered contrary to conscience and common sense. Tariqa Syadziliyah becomes something interesting, because it is not only related to religious rituals, but also has influences in the socio-cultural and economic fields. The focus of this research is 1) How does Pondok PETA apply moderation in teaching thariqa Syadziliyah? 2) How does Pondok Peta apply moderation in socio-cultural life? 3) How does Pondok PETA apply moderation in the economic field? While the purpose of answering the research’s focus is to 1) Analyze and describe the religious practices of the Syadziliyah Congregation at Pondok PETA developing into a culture of the Tulungagung community. 2) Analyzing and describing social life, economic empowerment of the Syadzililiyah congregation. This study uses a qualitative method with an ethnographic approach in collecting data. Using social construction theory from Peter Berger and Thomas Luckman, moderation theory, and AGIL from Talcott Parsons as his analytical tools. This study found that Pondok PETA was able to adapt to the conditions of the times by modifying the practices of the tarekat without sacrificing the nature of their teachings. Socio-cultural moderation in Pondok PETA is attempted by making the congregation human beings who are humble, not concerned with the worldly, while at the same time teaching respect for different people. The practices that are practiced are made to maintain the behavior of the congregation in accordance with the teachings of the lodge, even though they are far from the Murshid. Economic moderation is achieved through the modern KSPPS BMT PETA which functions as a data collection and development program, while for the congregation to improve welfare, istiqomah, reverence for teachers and increase spiritual piety.